Special Health Insurance as an Inclusive Social Protection Program for People with Disabilities - Kafaa, Kafa Abdallah (Jurnal Ilmiah Peuradeun, 2021)
The article illustrated the intervention of government within poverty alleviation through inclusive social protection for People With Disabilities. By studying Special Health Insurance program in the Special Region of Yogyakarta, it assumes that the existence of the program has occurred from a rights-based perspective in inclusive health configuration. It is based on the case study approach that aimed to explain the Special Health Insurance program implementation to extend coverage to all People With Disabilities. The main result provided the Special Health Insurance-integrated scheme program can be more inclusively and accessible for People With Disabilities than former social protection programs in Indonesia. It has finally provided the best practice for the social protection program as a social policy tool focusing on disability.